2015
DOI: 10.1242/jcs.175158
|View full text |Cite
|
Sign up to set email alerts
|

Outside-in signaling – a brief review of GPCR signaling with a focus on the Drosophila GPCR family

Abstract: G-protein-coupled receptors (GPCRs) are the largest family of receptors in many organisms, including worms, mice and humans. GPCRs are seven-transmembrane pass proteins that are activated by binding a stimulus (or ligand) in the extracellular space and then transduce that information to the inside of the cell through conformational changes. The conformational changes activate heterotrimeric G-proteins, which execute the downstream signaling pathways through the recruitment and activation of cellular enzymes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 90 publications
2
120
0
1
Order By: Relevance
“…Intriguingly, many ciliary receptors identified to date are GPCRs (Table 1A). The biology of GPCR signaling has been reviewed in detail elsewhere (see [8]). Briefly, about 800 different GPCRs are expressed in humans and almost half of all therapeutic drugs target GPCRs, creating considerable medical and commercial interest.…”
Section: Ciliary Gpcr Signalingmentioning
confidence: 99%
“…Intriguingly, many ciliary receptors identified to date are GPCRs (Table 1A). The biology of GPCR signaling has been reviewed in detail elsewhere (see [8]). Briefly, about 800 different GPCRs are expressed in humans and almost half of all therapeutic drugs target GPCRs, creating considerable medical and commercial interest.…”
Section: Ciliary Gpcr Signalingmentioning
confidence: 99%
“…The mth/mthl included in our analysis were: four sequences from An. gambiae (Hill et al ., ), 16 sequences from D. melanogaster (Hanlon and Andrew, ), four sequences from T. castaneum (Li et al ., ), four sequences from B. mori (Fan et al ., ) and two sequences from Ap. mellifera (Li et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…[161] Conformational change Another mechanism to transduce signals across am embrane is based on biological transmembrane receptors, such as the GPCR superfamily.B inding of al igand induces ac onformational change in the receptor,p ropagated across the membrane, ChemBioChem 2019ChemBioChem , 20,2569ChemBioChem -2580 www.chembiochem.org resultingi nt he activation of ar eceptor-associated proteins, which transmits the signalfurtherdownstream. [162][163][164][165][166][167][168][169][170] In ab id to achievet his type of signalling using an artificial receptor,W ebb and Clayden initially demonstrated that a chiral ligand interacting with an aminoisobutyric acid (Aib) helical foldamer could induce overall changes in the handedness of the helix, therebyc ommunicating as ignal over several nanometers ( Figure 5D). [171][172][173] Following up on this work, this team modified one terminus of the helical foldamer with a photo-responsive azobenzene motif.…”
Section: Receptor Oligomerisationmentioning
confidence: 99%